Fertigation with Zn-Lysine Confers Better Photosynthetic Efficiency and Yield in Water Stressed Maize: Water Relations, Antioxidative Defense Mechanism and Nutrient Acquisition - Faisal Shehzad; Qasim Ali; Shafaqat Ali; Fahad A. Al-Misned; Saliha Maqbool (Plants, 2022)
Different strategies including the exogenous use of micronutrient-chelated amino acids are being employed for better crop yield with limited fresh water for irrigation. The present study was conducted to assess the effects of foliar-applied Zn-lysine (Zn-Lys) on maize growth and yield under limited irrigation, in relation to physio-biochemical mechanisms such as the plant–water relations, photosynthetic efficiency, antioxidant defense mechanism, amino acid accumulation and nutrient acquisition. The experiment comprised two maize cultivars (MMRI and Pearl), two irrigation levels and three levels of Zn-Lys (0.25, 0.5 and 0.75%). Zn-Lys fertigation was found to be effective in reducing the negative impacts of limited water supply on grain yield, associated with improved photosynthetic efficiency, water relations, antioxidative defense mechanism and reduced lipid peroxidation in both maize cultivars. Zn-Lys-induced improvement in antioxidative mechanisms was associated with improved content of non-enzymatic antioxidants and activities of antioxidant enzymes. Foliar-fertigation with Zn-Lys also significantly improved the contents of various amino acids including Lys, as well as uptake of nutrients in both maize cultivars. In conclusion, the 0.5% level of Zn-Lys was found to be effective in ameliorating the negative impacts of water stress for better grain yield in both maize cultivars that can also be used as an important environment-friendly source of Zn to fulfill maize Zn deficiency.